How Does Brand Awareness Mediate the Influence of TikTok Shop Testimonials and Brand Image on Purchase Intention? A Case Study of DKI Jakarta - Tanto Adi Pangestu; Ilza Febrina; Mas Sridjoko Darodjatun (International Journal of Entrepreneurship, Business, and Creative Economy, 2026)
The rapid rise of TikTok Shop as an e-commerce channel has introduced new dynamics in how consumers interact with brands and make purchasing decisions. With its integration of short-form video content and seamless in-app shopping features, TikTok Shop has transformed traditional online shopping into a more interactive, content-driven experience. This evolution has heightened the importance of user testimonials and brand presentation within the platform, especially in shaping consumer perceptions and behaviors. Given this shift, it is essential to explore how such factors operate in specific market contexts. Accordingly, this study aims to examine the influence of TikTok Shop testimonials and brand image on brand awareness and online purchase intention among consumers in DKI Jakarta.  A self-administered survey was conducted with a sample of 140 respondents and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that brand image significantly enhances brand awareness but does not directly impact purchase intention. Meanwhile, brand awareness plays a crucial mediating role, positively influencing purchase intention. Social media testimonials contribute to brand awareness but have an insignificant direct effect on purchase intention. These results highlight the importance of brand awareness in shaping consumer decisions and provide valuable implications for businesses to optimize their digital marketing strategies by leveraging customer testimonials and strengthening brand identity to enhance consumer engagement and purchasing behavior.